2015
DOI: 10.1590/0037-8682-0205-2015
|View full text |Cite
|
Sign up to set email alerts
|

Severe dengue in the early postoperative period after kidney transplantation: two case reports from Hospital Geral de Fortaleza

Abstract: Dengue is an arbovirosis that ranges from an asymptomatic presentation to a more severe disease, which is characterized by a vascular leakage syndrome where abdominal pain is a major symptom. Transplant recipients are immunosuppressed and are less likely to develop a severe form of the disease because of a reduction in immune-mediated responses that trigger plasma extravasation events. Herein, we report two cases of severe dengue in the early postoperative period of two kidney transplant recipients. Considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…We reviewed two large cross sectional studies, three case series and four case reports. In one study only the abstract was available [11], and in the other immunosuppression protocol was absent [12], however we used data on symptomatology, lab investigations and mortality. The total number of subjects described in literature was 168.…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed two large cross sectional studies, three case series and four case reports. In one study only the abstract was available [11], and in the other immunosuppression protocol was absent [12], however we used data on symptomatology, lab investigations and mortality. The total number of subjects described in literature was 168.…”
Section: Resultsmentioning
confidence: 99%
“…Studies had shown that approximately 8.9% mortality was associated with dengue infection among renal transplant recipients [11]. In some cases mortality is a direct effect of bleeding [2], while others were due to secondary causes (for example, sepsis, type 1 respiratory failure) [7, 8]. …”
Section: Discussionmentioning
confidence: 99%
“…Here we report a case of DF in a post kidney transplant patient in a background of chronic active hepatitis B infection. Information on confirmed cases of DF among solid organ transplant recipients in the literature is limited, with very few fatalities; most of the fatalities occurring during the immediate post transplant period [2, 4]. Complete recovery of a post liver transplant recipient with DF was reported locally [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, case reports generally show dengue as a severe disease in immunocompromised patients with mortality rates >40% . On the other hand, dengue case series have shown that the disease can be mild in some transplant populations, such as kidney recipients .…”
Section: Discussionmentioning
confidence: 99%